The English Language and Cultural Appropriateness - Misso, Vannessa; Maadad, Nina (SOSIOHUMANIKA, 2011)
ABSTRACT: English language acquisition needs to be taught from a multi-ethnic and multi-cultural perspective, with the right teaching materials, when pursuing cultural sensitivity and equality. After a brief historical overview and an explanation of the various definitions associated with English language acquisition, English is described in its multiple varieties. It is increasingly contended that non-native English speakers outnumber native speakers in a rapidly globalising world. Case studies are used to justify the need for culturally appropriate teaching materials and the challenges that exist. Change has been slow in addressing the inadequacies in current teaching materials and this paper concludes by suggesting some bottom-up approaches will transform the teaching pedagogy and teachersâ attitudes. The professional development of teachers, together with the support of enlightened linguistic researchers can perhaps lead to an educational philosophy that cuts across colour, creed and race to bring about success to language learners. Thus, creating a better understanding of the English language in the context of cultural appropriateness.Key words: English language, non-native English speakers, bottom-up approaches, and better understanding of the English language.About the Authors: Dr. Vannessa Misso and Dr. Nina Maadad are Lecturers at the School of Education UOA (University of Adelaide), Australia. One of them, for academic purposes, can be reached at: nina.maadad@adelaide.edu.auHow to cite this article? Misso, Vannessa & Dr. Nina Maadad. (2011). âThe English Language and Cultural Appropriatenessâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.4, No.1 [Mei], pp.111-128. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-0112. Chronicle of article: Accepted (March 27, 2011); Revised (April 29, 2011); and Published (May 20, 2011). Â  Â